A comparison of estimated glomerular filtration rates using Cockcroft−Gault and the Chronic Kidney Disease Epidemiology Collaboration estimating equations in HIV infection. Issue 3 (3rd October 2013) - Mocroft, A; Ryom, L; Reiss, P; Furrer, H; D'Arminio Monforte, A; Gatell, J; de, S; Beniowski, M; Lundgren, JD; Kirk, O; ,
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to determine whether the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI)‐ or Cockcroft−Gault (CG)‐based estimated glomerular filtration rates (eGFRs) performs better in the cohort setting for predicting moderate/advanced chronic kidney disease (CKD) or end‐stage renal disease (ESRD). Methods A total of 9521 persons in the EuroSIDA study contributed 133 873 eGFRs. Poisson regression was used to model the incidence of moderate and advanced CKD (confirmed eGFR < 60 and < 30 mL/min/1.73 m2, respectively) or ESRD (fatal/nonfatal) using CG and CKD‐EPI eGFRs. Results Of 133 873 eGFR values, the ratio of CG to CKD‐EPI was ≥ 1.1 in 22 092 (16.5%) and the difference between them (CG minus CKD‐EPI) was ≥ 10 mL/min/1.73 m2 in 20 867 (15.6%). Differences between CKD‐EPI and CG were much greater when CG was not standardized for body surface area (BSA). A total of 403 persons developed moderate CKD using CG [incidence 8.9/1000 person‐years of follow‐up (PYFU); 95% confidence interval (CI) 8.0–9.8] and 364 using CKD‐EPI (incidence 7.3/1000 PYFU; 95% CI 6.5–8.0). CG‐derived eGFRs were equal to CKD‐EPI‐derived eGFRs at predicting ESRD (n = 36) and death (n = 565), as measured by the Akaike information criterion. CG‐based moderate and advanced CKDs were associated with ESRD [adjusted incidence rate ratio (aIRR) 7.17; 95% CI 2.65–19.36 and aIRR 23.46; 95% CI 8.54–64.48, respectively], as were CKD‐EPI‐based moderate and advanced CKDs (aIRR 12.41; 95% CI 4.74–32.51 and aIRR 12.44; 95% CI 4.83–32.03, respectively). Conclusions Differences between eGFRs using CG adjusted for BSA or CKD‐EPI were modest. In the absence of a gold standard, the two formulae predicted clinical outcomes with equal precision and can be used to estimate GFR in HIV‐positive persons.